Analisis Dampak Kebijakan Program Kebun Sekolah untuk Mengatasi Kekurangan Gizi pada Anak - Permana, Deni (FIA Unkris Press, 2023)
The school garden program has been implemented as one of the efforts to address malnutrition among children. This analysis aims to evaluate the impact of the policy on students' nutritional status and its effectiveness in increasing nutritious food intake. The study involved data collection through surveys, interviews, and measurement of nutritional status before and after the implementation of the program. The results of the analysis show that school gardens have a positive impact in improving students' knowledge about nutrition and healthy eating. Students were directly involved in the process of planting and caring for the plants, which contributed to increased consumption of fresh fruits and vegetables. The program also plays a role in reducing the prevalence of malnutrition, with a significant increase in the weight and height of children involved in the school garden. However, the success of the program is influenced by several factors, including support from the school, parental involvement, and accessibility of resources. Constraints included budget limitations and lack of training for educators on how to effectively manage school gardens. To improve the effectiveness of the program, it is recommended that the policy be complemented with adequate training, stable financial support, and integration with the health education curriculum.Overall, school gardens are a promising strategy to address undernutrition